SEMANTIC CHANGES IN RUSSIAN ANGLICISMS DURING THE PERIOD OF MILLENNIAL EVENTS IN RUSSIAN SOCIETY (Živi jezici: Journal for Foreign Languages and Literatures, 2025)
The aim of this study was to explore the nature and directions of current and dynamic semantic processes within the structure of Russian Anglicisms that occurred from the late 1970s until almost the present day, placing these two temporal boundaries in a comparative relationship, which lends the research a comparative-historical dimension. This relatively short period was chosen due to the turbulent and substantial changes that have affected the Russian society. Such socially conditioned changes have proven to be functional external factors in the development of the contemporary Russian language. We selected Anglicisms as an etymologically special lexical layer of contemporary Russian to observe how they behave during a period when the results of all-encompassing activities of a society, composed of speakers for whom English is the native language, experience global expansion and popularity. The research has revealed the presence of most of the semantic processes defined by linguistics for the transition from the 20th to the 21st century, while also isolating some new ones, which represents the greatest contribution of this study. For most of these processes, sociological comments were also provided—specific social phenomena that led to certain changes in the semantic structure of Anglicisms.
Keywords: types of semantic changes; Anglicisms; contemporary Russian language; changes in Russian society at the turn of the 20th to the 21st century; comparative-historical approach